COVID-19 vaccination acceptance among community members and health workers in Ebonyi state, Nigeria: study protocol for a concurrent-independent mixed method analyses of intention to receive, timeliness of the intention to receive, uptake and hesitancy to COVID-19 vaccination and the determinants - Ugwu I Omale; Osarhiemen Iyare; Richard L Ewah; Chidinma I Amuzie; Onyinyechukwu U Oka; Victor U Uduma; Azuka S Adeke; Cordis O Ikegwuonu; Olaedo O Nnachi; Okechukwu O Ukpabi; Ifeyinwa M Okeke; Glory E Nkwo; et al. (BMJ Open)
Introduction The COVID-19 pandemic has gravely affected the lives and economies of the global population including Nigeria. The attainment of herd immunity through mass COVID-19 vaccination is the foremost control strategy, however, the deployments of COVID-19 vaccinations are facing challenges of non-acceptance. Despite the efforts of the Nigerian government and COVAX facility in making COVID-19 vaccination more available/accessible, the vaccination rate remains unexpectedly very low in Nigeria/Ebonyi state. Therefore, it is important to investigate the acceptability of COVID-19 vaccination to elucidate the explanations for the very low coverage rate. This study aims to evaluate/explore COVID-19 vaccination acceptance and the determinants among community members and health workers in Ebonyi state, Nigeria.Methods and analyses The study is an analytical cross-sectional survey with a concurrent-independent mixed method design. Quantitative data will be collected from all consenting/assenting community members aged 15 years and above, in 28 randomly selected geographical clusters, through structured interviewer-administered questionnaire household survey using KoBoCollect installed in android devices. Quantitative data will be collected from all consenting health workers, selected via convenience and snowball techniques, through structured self-administered questionnaire survey distributed via WhatsApp and interviewer-administered survey using KoBoCollect installed in android devices. Qualitative data will be collected from purposively selected community members and health workers through focus group discussions. Quantitative analyses will involve descriptive statistics, generalised estimating equations (for community members data) and generalised linear model (for health workers data). Qualitative analyses will employ the thematic approach.Ethics and dissemination Ethical approval for this study was obtained from the Ebonyi State Health Research and Ethics Committee (EBSHREC/15/01/2022–02/01/2023) and Research and Ethics Committee of Alex Ekwueme Federal University Teaching Hospital Abakaliki (14/12/2021–17/02/2022), and verbal consent will be obtained from participants. Study findings will be reported at local, national and international levels as appropriate.Trial registration number ISRCTN16735844.